Preparation method and application of bimetallic MOF-CMC aerogel composite materials

By preparing bimetallic MOF-CMC aerogel composites, the problems of poor stability and high cost of heavy metal adsorbents in the prior art are solved, and efficient adsorption and environmentally friendly regeneration of Cu2+, Pb2+, and Cd2+ are achieved, thereby reducing production costs.

CN116212833BActive Publication Date: 2025-01-10QINGDAO UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310388893.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-13
Publication Date
2025-01-10
Estimated Expiration
2043-04-13

AI Technical Summary

Technical Problem

The existing heavy metal adsorbents exist in powder form, have poor stability, limited adsorption capacity, and are cost-effective, making it difficult to effectively remove contaminants such as Cu2+, Pb2+, Cd2+ in water bodies.

Method used

Using the preparation method of bimetallic MOF-CMC aerogel composite, PET plastic pyrolyzed to obtain terephthalic acid by hydrothermal method, and reacted with cobalt and nickel metal salts in DMF solution, combined with CMC aerogel to form Nickel-cobalt bimetallic MOF-CMC aerogel composite material enhances its adsorption ability and structural stability.

Benefits of technology

It improves the adsorption capacity of Cu2+, Pb2+, and Cd2+, reduces production costs, and has a stable material structure and is suitable for reuse. It solves the problem of regeneration and reuse of traditional adsorbents and achieves the environmental protection effect of "waste control waste".

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004175130050000011
    Figure HDA0004175130050000011
  • Figure HDA0004175130050000012
    Figure HDA0004175130050000012
  • Figure HDA0004175130050000013
    Figure HDA0004175130050000013
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a bimetallic MOF-CMC aerogel composite material, the preparation method comprising the following steps: pyrolyzing PET plastic by a hydrothermal method to obtain terephthalic acid; dissolving cobalt metal salt, nickel metal salt and terephthalic acid in a DMF solution to obtain a clear solution, wherein the molar ratio of the total amount of the cobalt metal salt and the nickel metal salt to terephthalic acid is 1:3 to 3:1; placing the CMC aerogel in a stainless steel reactor, adding the obtained clear solution, and reacting at 80 to 160°C for 12 to 20 hours; after the reaction is completed, washing the obtained primary product with DMF for multiple times, activating it with alcohol within two days, and then freezing and drying it to obtain a nickel-cobalt bimetallic MOF-CMC aerogel composite material. The composite material prepared by the present invention can improve the adsorption capacity of the adsorbent, reduce costs, and solve the problem of plastic pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a preparation method and application of a bimetallic MOF-CMC aerogel composite material. Background Art

[0002] With the development of industry, water pollution is becoming more and more serious. Among them, heavy metal pollution, especially Cu 2+ , Pb 2+ 、Cd 2+ Pollution problems such as Cu can not be ignored. 2+ , Pb 2+ 、Cd 2+ etc. are heavy metal ions with high toxicity and serious pollution in the environment. Since heavy metal ions are non-biodegradable and can exist in the environment for a long time, for the sake of human health, it is necessary to effectively solve the heavy metal pollution, especially Cu 2+ , Pb 2+ 、Cd 2+ Pollution problems such as heavy metal ions are an important topic today. Adsorption is simple to operate and has low energy consumption. It is one of the important methods for removing heavy metal ions from water. The key to improving the ability of adsorption to remove pollutants lies in the research and development of new adsorbents. At present, the main problems of traditional heavy metal adsorbents are: (1) Most adsorbents exist in powder form, which is difficult to regenerate and reuse; (2) The adsorbent has limited adsorption capacity for target pollutants; (3) The adsorbent is expensive.

[0003] In recent years, emerging metal-organic frameworks (MOFs) are porous crystalline materials with a periodic network structure formed by self-assembly of multi-dentate organic ligands and metal coordination centers (metal ions or metal clusters). 2 / g), large porosity, structural diversity, good thermal stability, etc., and show excellent performance in the adsorption of heavy metal ions in water. However, most MOFs materials exist in powder form, with poor skeleton stability and easy collapse after contact with water. Moreover, their atomic density is low and they have completely open pore space, which has huge defects in adsorption capacity and the ability to capture small molecules, which seriously limits their application in the field of water treatment. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a preparation method and application of a bimetallic MOF-CMC aerogel composite material, so as to achieve the purpose of improving the adsorption capacity of the adsorbent, reducing costs and solving the problem of plastic pollution.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing a bimetallic MOF-CMC aerogel composite material comprises the following steps:

[0007] Step (1), pyrolyzing PET plastic by a hydrothermal method to obtain terephthalic acid;

[0008] Step (2), dissolving a cobalt metal salt, a nickel metal salt and terephthalic acid in a DMF solution to obtain a clear solution, wherein the molar ratio of the total amount of the cobalt metal salt and the nickel metal salt to the terephthalic acid is 1:3 to 3:1;

[0009] Step (3), placing the CMC aerogel in a stainless steel reactor, adding the obtained clear solution, and reacting at 80-160° C. for 12-20 hours;

[0010] Step (4), after the reaction is completed, the obtained initial product is washed with DMF for multiple times, activated with alcohol within two days, and then frozen and dried to obtain a nickel-cobalt bimetallic MOF-CMC aerogel composite material.

[0011] In the above scheme, the specific method of step (1) is as follows: PET plastic is cut into pieces, washed, and dried for later use; then 2.5 g of PET plastic, 5 mL of ethylene glycol, and 50 mL of deionized water are placed in a polytetrafluoroethylene-lined high-pressure reactor, and reacted at 180 to 230° C. for 4 to 10 hours. After the reaction is completed, the obtained terephthalic acid is centrifuged, washed, and dried.

[0012] In the above scheme, the preparation method of the CMC aerogel is as follows: carboxymethyl cellulose is added to deionized water, stirred continuously to dissolve it, and ultrasonically dispersed to obtain a transparent uniform colloid, after removing bubbles, the obtained colloid is transferred to a well plate and aged to form a CMC aerogel precursor; the CMC aerogel precursor is frozen and dried to obtain the CMC aerogel.

[0013] In the above scheme, the cobalt metal salt is a nitrate or a chloride, and the nickel metal salt is a chloride.

[0014] Preferably, the molar ratio of the total amount of the cobalt metal salt and the nickel metal salt to terephthalic acid is 1:1.

[0015] In a further technical solution, the molar ratio of the cobalt metal salt to the nickel metal salt is 3:7 to 7:3.

[0016] Preferably, the molar ratio of the cobalt metal salt to the nickel metal salt is 5:5.

[0017] Preferably, in step (3), the reaction temperature is 120° C. and the reaction time is 14 h.

[0018] In the above scheme, in step (4), the alcohol used for activation is methanol or ethanol.

[0019] Application of the nickel-cobalt bimetallic MOF-CMC aerogel composite material prepared by the preparation method as described above in the adsorption of heavy metal ions.

[0020] Through the above technical scheme, the preparation method of a bimetallic MOF-CMC aerogel composite material provided by the present invention has the following beneficial effects:

[0021] (1) The present invention introduces bimetallic MOF into CMC aerogel by in-situ growth method, which fully combines the advantages of bimetallic MOF and CMC aerogel. Different metal sites in Ni-Co bimetallic MOFs can produce excellent synergistic effects, enhancing their Cu 2+ , Pb 2+ 、Cd 2+ CMC aerogel is a porous material with a three-dimensional network and good stability. There are hydrogen bonds in the cross-linked CMC aerogel structure, which has high thermal stability and is suitable for Cu 2+ , Pb 2+ 、Cd 2+ The present invention combines the two, and the obtained adsorbent has good adsorption on Cu 2+ , Pb 2+ 、Cd 2+ Etc. strong removal ability.

[0022] (2) The nickel-cobalt bimetallic MOF-CMC aerogel composite material prepared by the present invention has a three-dimensional macroscopic structure, is stable, is not easy to decompose, can be reused, and reduces production costs. During the material preparation process, CMC aerogel can provide a large number of binding sites for the growth of MOFs, and can also enhance the mechanical strength of MOFs and improve their regeneration and reuse performance.

[0023] (3) The nickel-cobalt bimetallic MOF-CMC aerogel composite material prepared by the present invention uses PET plastic as the source of organic ligands in the MOF preparation process, and then synthesizes the adsorbent for Cu in wastewater 2+ , Pb 2+ 、Cd 2+ The adsorption of plastics, etc., "using waste to treat waste", can alleviate the harm of plastic pollution to the environment, and can reduce the cost of the prepared adsorbent. At the same time, cellulose, which has the advantages of wide sources, large reserves, green and environmental protection, biodegradability and processability, is used as one of the main raw materials for adsorbent synthesis, which is green and environmentally friendly and can reduce the cost of adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below.

[0025] Figure 1 This is a photo of the appearance of the composite material prepared in Example 1 of the present invention;

[0026] Figure 2 FT-IR comparison chart of terephthalic acid, CMC aerogel and Ni / Co-MOF-CMC prepared in Example 1;

[0027] Figure 3 The Ni / Co-MOF-CMC prepared in Example 1 and its adsorption of Cu 2+ SEM images after treatment; (a) Ni / Co-MOF-CMC, (b) Ni / Co-MOF-CMC-Cu 2+ ; (c) is a partial enlarged view of (b);

[0028] Figure 4 The CMC aerogel, Ni / Co-MOF-CMC and Ni / Co-MOF-CMC-Cu prepared in Example 1 2+ XPS comparison chart;

[0029] Figure 5 Ni / Co-MOF-CMC prepared in Example 1 adsorbs Cu 2+ The adsorption equilibrium curve. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0031] The present invention provides a method for preparing a nickel-cobalt bimetallic MOF-CMC aerogel composite material (Ni / Co-MOF-CMC), and the specific embodiments are as follows:

[0032] Example 1

[0033] 1. A method for preparing a nickel-cobalt bimetallic MOF-CMC aerogel composite material (Ni / Co-MOF-CMC), comprising the following steps:

[0034] (1) Remove the label and bottle cap from a PET plastic bottle, cut into small flakes, wash, and dry at 60°C for later use; then place the flakes (2.5 g), ethylene glycol (5 mL), and deionized water (50 mL) in a polytetrafluoroethylene-lined autoclave, and keep at 180°C for 10 h, centrifuge, wash, and dry at 60°C to obtain terephthalic acid.

[0035] (2) 1 g of carboxymethyl cellulose (CMC) was added to 15 mL of deionized water and stirred continuously to dissolve it; then 15 mL of deionized water was added to the mixed solution and ultrasonically dispersed to obtain a transparent and uniform colloid; after removing bubbles, the obtained colloid was transferred to a 96-well plate and aged for 1 hour to form a CMC aerogel precursor; the CMC aerogel precursor was frozen and dried for 12 hours to obtain a CMC aerogel.

[0036] (3) 0.29 g Co(NO 3 ) 2 6H 2 O, 0.24 g NiCl 2 6H 2 O and 0.99 g H 2 BDC (terephthalic acid) was dissolved in 51.2 mL of DMF to obtain a clear solution, which was recorded as solution A.

[0037] (4) The CMC aerogel cylinder prepared in step (2) was placed in a 100 mL polytetrafluoroethylene-lined stainless steel reactor, solution A prepared in step (3) was added, and heated at 120° C. for 14 h to obtain a primary product of a Ni / Co-MOF-CMC three-dimensional composite material.

[0038] (5) The initial product obtained in step (5) was washed with DMF for multiple times, and activated by exchanging the solvent with methanol (dehydrogenation) for 3 times within two days, and then frozen and dried for 12 hours to obtain a Ni / Co-MOF-CMC three-dimensional composite material.

[0039] Example 2

[0040] 1. A method for preparing a cobalt-nickel bimetallic MOF-CMC aerogel three-dimensional composite material (Ni / Co-MOF-CMC), comprising the following steps:

[0041] (1) Remove the label and bottle cap from a PET plastic bottle, cut into small flakes, wash, and dry at 60°C for later use; then place the flakes (2.5 g), ethylene glycol (5 mL), and deionized water (50 mL) in a polytetrafluoroethylene-lined autoclave, and keep at 230°C for 4 hours, centrifuge, wash, and dry at 60°C to obtain terephthalic acid.

[0042] (2) 1 g of carboxymethyl cellulose (CMC) was added to 15 mL of deionized water and stirred continuously to dissolve it; then 15 mL of deionized water was added to the mixed solution and ultrasonically dispersed to obtain a transparent and uniform colloid; after removing bubbles, the obtained colloid was transferred to a 96-well plate and aged for 1 hour to form a CMC aerogel precursor; the CMC aerogel precursor was freeze-dried for 12 hours to obtain CMC aerogel.

[0043] (3) 0.87 g Co(NO 3 ) 2 6H 2 O, 0.72 g NiCl 2 6H 2 O and 0.33 g H 2 BDC (terephthalic acid) was dissolved in 51.2 mL of DMF to obtain a clear solution, which was recorded as solution A.

[0044] (4) The CMC aerogel cylinder prepared in step (2) was placed in a 100 mL polytetrafluoroethylene-lined stainless steel reactor, solution A prepared in step (3) was added, and heated at 80° C. for 20 h to obtain a primary product of a Ni / Co-MOF-CMC aerogel three-dimensional composite material.

[0045] (5) The initial product obtained in step (5) was washed with DMF for multiple times, and activated by exchanging the solvent with ethanol (dehydrogenation) for 3 times within two days, and then frozen and dried for 12 hours to obtain a Ni / Co-MOF-CMC aerogel three-dimensional composite material.

[0046] Example 3

[0047] 1. A method for preparing a nickel-cobalt bimetallic MOF-CMC aerogel three-dimensional composite material (Ni / Co-MOF-CMC), comprising the following steps:

[0048] (1) Remove the label and bottle cap from a PET plastic bottle, cut into small flakes, wash, and dry at 60°C for later use; then place the flakes (2.5 g), ethylene glycol (5 mL), and deionized water (50 mL) in a polytetrafluoroethylene-lined autoclave, and keep at 180°C for 4 hours, centrifuge, wash, and dry at 60°C to obtain terephthalic acid.

[0049] (2) 1 g of carboxymethyl cellulose (CMC) was added to 15 mL of deionized water and stirred continuously to dissolve it; then 15 mL of deionized water was added to the mixed solution and ultrasonically dispersed to obtain a transparent and uniform colloid; after removing bubbles, the obtained colloid was transferred to a 96-well plate and aged for 1 hour to form a CMC aerogel precursor; the CMC aerogel precursor was freeze-dried for 12 hours to obtain CMC aerogel.

[0050] (3) 0.29 g CoCl 2 6H 2 O, 0.24 g NiCl 2 6H 2 O and 0.33 g H 2 BDC (terephthalic acid) was dissolved in 51.2 mL of DMF to obtain a clear solution, which was recorded as solution A.

[0051] (4) The CMC aerogel cylinder prepared in step (2) was placed in a 100 mL polytetrafluoroethylene-lined stainless steel reactor, solution A prepared in step (3) was added, and heated at 120° C. for 16 h to obtain a primary product of a Ni / Co-MOF-CMC aerogel three-dimensional composite material.

[0052] (5) The initial product obtained in step (5) was washed with DMF for multiple times, and activated by exchanging the solvent with methanol (dehydrogenation) for 3 times within two days, and then frozen and dried for 12 hours to obtain a Ni / Co-MOF-CMC aerogel three-dimensional composite material.

[0053] Example 4

[0054] 1. A method for preparing a nickel-cobalt bimetallic MOF-CMC aerogel three-dimensional composite material (Ni / Co-MOF-CMC), comprising the following steps:

[0055] (1) Remove the label and bottle cap from a PET plastic bottle, cut into small flakes, wash, and dry at 60°C for later use; then place the flakes (2.5 g), ethylene glycol (5 mL), and deionized water (50 mL) in a polytetrafluoroethylene-lined autoclave, and keep at 230°C for 10 h, centrifuge, wash, and dry at 60°C to obtain terephthalic acid.

[0056] (2) 1 g of carboxymethyl cellulose (CMC) was added to 15 mL of deionized water and stirred continuously to dissolve it; then 15 mL of deionized water was added to the mixed solution and ultrasonically dispersed to obtain a transparent and uniform colloid; after removing bubbles, the obtained colloid was transferred to a 96-well plate and aged for 1 hour to form a CMC aerogel precursor; the CMC aerogel precursor was freeze-dried for 12 hours to obtain a CMC aerogel.

[0057] (3) 0.18 g CoCl 2 6H 2 O, 0.33 g NiCl 2 6H 2 O and 0.33 g H 2 BDC (terephthalic acid) was dissolved in 51.2 mL of DMF to obtain a clear solution, which was recorded as solution A.

[0058] (4) The CMC aerogel cylinder prepared in step (2) was placed in a 100 mL polytetrafluoroethylene-lined stainless steel reactor, solution A prepared in step (3) was added, and heated at 160° C. for 14 h to obtain a primary product of a Co / Ni-MOF-CMC aerogel three-dimensional composite material.

[0059] (5) The initial product obtained in step (5) was washed with DMF for multiple times, and activated by exchanging the solvent with ethanol (dehydrogenation) for 3 times within two days, and then freeze-dried for 12 hours to obtain a Ni / Co-MOF-CMC aerogel three-dimensional composite material.

[0060] Example 5

[0061] 1. A method for preparing a nickel-cobalt bimetallic MOF-CMC aerogel three-dimensional composite material (Ni / Co-MOF-CMC), comprising the following steps:

[0062] (1) Remove the label and bottle cap from a PET plastic bottle, cut into small flakes, wash, and dry at 60°C for later use; then place the flakes (2.5 g), ethylene glycol (5 mL), and deionized water (50 mL) in a polytetrafluoroethylene-lined autoclave, and keep at 210°C for 8 h, centrifuge, wash, and dry at 60°C to obtain terephthalic acid.

[0063] (2) 1 g of carboxymethyl cellulose (CMC) was added to 15 mL of deionized water and stirred continuously to dissolve it; then 15 mL of deionized water was added to the mixed solution and ultrasonically dispersed to obtain a transparent and uniform colloid; after removing bubbles, the obtained colloid was transferred to a 96-well plate and aged for 1 hour to form a CMC aerogel precursor; the CMC aerogel precursor was freeze-dried for 12 hours to obtain CMC aerogel.

[0064] (3) 0.41 g Co(NO 3 ) 2 6H 2 O, 0.14 g NiCl 2 6H 2 O and 0.33 g H 2 BDC (terephthalic acid) was dissolved in 51.2 mL of DMF to obtain a clear solution, which was recorded as solution A.

[0065] (4) The CMC aerogel cylinder prepared in step (2) was placed in a 100 mL polytetrafluoroethylene-lined stainless steel reactor, solution A prepared in step (3) was added, and heated at 120° C. for 12 h to obtain a primary product of a Co / Ni-MOF-CMC aerogel three-dimensional composite material.

[0066] (5) The initial product obtained in step (5) was washed with DMF for multiple times, and activated by exchanging the solvent with methanol (dehydrogenation) for 3 times within two days, and then freeze-dried for 12 hours to obtain a Ni / Co-MOF-CMC aerogel three-dimensional composite material.

[0067] Comparative Example 1

[0068] The difference from Example 1 is that in step (3), 0.58 g Co(NO3 ) 2 6H 2 O and 0.99 g H 2 BDC (terephthalic acid) was dissolved in 51.2 mL DMF to obtain a clear solution, which was recorded as solution A. The remaining steps were the same as in Example 1.

[0069] Comparative Example 2

[0070] The difference from Example 1 is that in step (3), 0.58 g NiCl 2 6H 2 O and 0.99 g H 2 BDC (terephthalic acid) was dissolved in 51.2 mL DMF to obtain a clear solution, which was recorded as solution A. The remaining steps were the same as in Example 1.

[0071] application

[0072] The materials obtained in Examples 1-5 and Comparative Examples 1-2 were used for Cu 2+ , Pb 2+ 、Cd 2+ Adsorption of Cu 2 + , Pb 2+ 、Cd 2+ The initial concentration of the solution was 50 mg / L, the amount of adsorbent was 10 mg, and the Cu 2+ , Pb 2+ 、Cd 2+ The solution volume was 50 mL, the temperature was 25 °C, the pH was 5, and the adsorption time was 6 h. After the adsorption was completed, the supernatant was filtered with a 0.45 μm filter membrane and the residual Cu was detected by atomic absorption. 2+ , Pb 2+ 、Cd 2+ The concentration was tested and the adsorbent was calculated to obtain the Cu 2+ , Pb 2+ 、Cd 2+ The adsorption capacities are shown in Table 1.

[0073] Table 1 Adsorption capacity of the adsorbent obtained in the examples and comparative examples (mg / g)

[0074] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 <![CDATA[Cu 2+ ]]> 100.2 89.4 92.5 78.7 100.3 55.5 55.9 <![CDATA[Pb 2+ ]]> 195.7 165.3 189.4 167.1 187.8 98.4 89.2 <![CDATA[Cd 2+ ]]> 94.3 76.9 86.2 73.5 90.8 48.2 47.4

[0075] It can be seen from the above table that the nickel-cobalt bimetallic MOF-CMC three-dimensional composite materials prepared in Examples 1-5 of the present invention have a good 2+ , Pb 2+ 、Cd 2+ They all have good adsorption properties, and the adsorption effect is significantly higher than that of nickel / cobalt single metal MOF-CMC three-dimensional composite material adsorbent.

[0076] Performance Characterization

[0077] 1. Appearance analysis

[0078] The appearance of the three-dimensional composite material prepared in Example 1 of the present invention is as follows Figure 1 As shown, it is a three-dimensional solid columnar structure. Compared with traditional powdered adsorbents, the adsorbent of the present invention is more conducive to regeneration and reuse.

[0079] 2. FT-IR analysis

[0080] The successful compounding of Ni-Co bimetallic MOF and CMC aerogel is the key to preparing the three-dimensional composite material of Co-Ni bimetallic MOF-CMC aerogel. Figure 2 The FT-IR comparison chart of terephthalic acid obtained by pyrolysis of PET, CMC aerogel and Ni / Co-MOF-CMC prepared in Example 1 is shown. Through FT-IR analysis, it is found that the peak shape of terephthalic acid obtained by pyrolysis of PET is basically consistent with that of commercial terephthalic acid, indicating that terephthalic acid has been successfully obtained by pyrolysis of PET plastic.

[0081] In addition, absorption peaks of cobalt-nickel metal oxide, carboxymethyl cellulose and terephthalic acid appeared in the nickel-cobalt bimetallic MOF-CMC aerogel three-dimensional composite material, indicating that the material has been successfully composited.

[0082] 3. SEM image

[0083] The SEM image of Ni / Co-MOF-CMC prepared in Example 1 is as follows: Figure 3 As shown in (a), the surface of Ni / Co-MOF-CMC is loose and porous, presenting a three-dimensional spatial network structure, which is conducive to full contact between pollutants and adsorbents and promotes the adsorption of pollutants.

[0084] Example 1 Ni / Co-MOF-CMC adsorbs Cu 2+ The SEM images after Figure 3 As shown in (b) and (c), Cu 2 + After that, obvious metal particles were deposited on the adsorbent surface, indicating that Cu 2+ It has been successfully adsorbed on the surface area of ​​Ni / Co-MOF-CMC.

[0085] 4. XPS chart

[0086] Figure 4 The CMC aerogel, Ni / Co-MOF-CMC and Ni / Co-MOF-CMC-Cu prepared in Example 1 2+ XPS comparison chart. Application of nickel-cobalt bimetallic MOF-CMC aerogel three-dimensional composite material for Cu 2+After the adsorption reaction is completed, the adsorbent will contain a certain amount of copper. Figure 4 As shown, the element content analysis obtained by XPS test found that the copper content in the adsorbent was 4.81%, which indicated that the adsorption reaction was successfully carried out.

[0087] 5. Adsorption equilibrium curve

[0088] Figure 5 Ni / Co-MOF-CMC prepared in Example 1 adsorbs Cu 2+ The adsorption equilibrium curve of Figure 5 It can be seen that its maximum theoretical adsorption capacity is 233.99 mg / g, which is significantly higher than the adsorption capacity of traditional adsorbents 0-100 mg / g.

[0089] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. Application of a bimetallic MOF-CMC aerogel composite material in adsorbing heavy metal ions, characterized in that: The preparation method of the composite material comprises the following steps: Step (1), pyrolyzing PET plastic by a hydrothermal method to obtain terephthalic acid; Step (2), dissolving a cobalt metal salt, a nickel metal salt and terephthalic acid in a DMF solution to obtain a clear solution, wherein the molar ratio of the total amount of the cobalt metal salt and the nickel metal salt to the terephthalic acid is 1:3 to 3:1; Step (3), placing the CMC aerogel in a stainless steel reactor, adding the obtained clear solution, and reacting at 80-160°C for 12-20 hours; Step (4), after the reaction is completed, the obtained initial product is washed with DMF for multiple times, activated with alcohol within two days, and then frozen and dried to obtain a nickel-cobalt bimetallic MOF-CMC aerogel composite material; The specific method of step (1) is as follows: cut the PET plastic into pieces, wash it, and dry it for later use; then place 2.5 g of the PET plastic, 5 mL of ethylene glycol, and 50 mL of deionized water in a polytetrafluoroethylene-lined high-pressure reactor, and react at 180-230° C. for 4-10 h. After the reaction is completed, centrifuge the obtained terephthalic acid, wash it, and dry it; The molar ratio of the cobalt metal salt to the nickel metal salt is 3:7 to 7:

3.

2. The use of a bimetallic MOF-CMC aerogel composite material in adsorbing heavy metal ions according to claim 1, characterized in that: The preparation method of the CMC aerogel is as follows: adding carboxymethyl cellulose into deionized water, stirring continuously to dissolve it, and uniformly dispersing it by ultrasonication to obtain a transparent uniform colloid; after removing bubbles, transferring the obtained colloid to a well plate and aging it to form a CMC aerogel precursor; freezing and drying the CMC aerogel precursor to obtain the CMC aerogel.

3. The use of a bimetallic MOF-CMC aerogel composite material in adsorbing heavy metal ions according to claim 1, characterized in that: The cobalt metal salt is a nitrate or a chloride, and the nickel metal salt is a chloride.

4. The use of a bimetallic MOF-CMC aerogel composite material in adsorbing heavy metal ions according to claim 1 or 3, characterized in that: The molar ratio of the total amount of the cobalt metal salt and the nickel metal salt to terephthalic acid is 1:

1.

5. The use of a bimetallic MOF-CMC aerogel composite material in adsorbing heavy metal ions according to claim 1 or 3, characterized in that: The molar ratio of the cobalt metal salt to the nickel metal salt is 5:

5.

6. The use of a bimetallic MOF-CMC aerogel composite material in adsorbing heavy metal ions according to claim 1, characterized in that: In step (3), the reaction temperature is 120°C and the reaction time is 14 h.

7. Use of a bimetallic MOF-CMC aerogel composite material in adsorbing heavy metal ions according to claim 1, characterized in that: In step (4), the alcohol used for activation is methanol or ethanol.

Citation Information

Patent Citations

  • Phosphorus slag-metal organic framework composite material as well as preparation method and application thereof

    CN114225908A